97.5k views
2 votes
How do you solve -3(x - 1) + 8(x - 3) = 6x + 7 -5x

User Debo
by
5.1k points

2 Answers

4 votes

Answer:

x = 7

Explanation:

Given

- 3(x - 1) + 8(x - 3) = 6x + 7 - 5x ← distribute parenthesis on left side and simplify

- 3x + 3 + 8x - 24 = x + 7

5x - 21 = x + 7 ( subtract x from both sides )

4x - 21 = 7 ( add 21 to both sides )

4x = 28 ( divide both sides by 4 )

x = 7

User Mike Gardiner
by
6.0k points
3 votes

Answer:

x=7

Explanation:

−3(x−1)+8(x−3)=6x+7−5x

(−3)(x)+(−3)(−1)+(8)(x)+(8)(−3)=6x+7+−5x(Distribute)

−3x+3+8x+−24=6x+7+−5x

(−3x+8x)+(3+−24)=(6x+−5x)+(7)(Combine Like Terms)

5x+−21=x+7

5x−21=x+7

Step 2: Subtract x from both sides.

5x−21−x=x+7−x

4x−21=7

Step 3: Add 21 to both sides.

4x−21+21=7+21

4x=28

Step 4: Divide both sides by 4.

4x/4=28/4

User Dan Mindru
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.